Antioxidants (in food, and their effects on health) - El Gammal, Ola ([cairo] author, 2025)
Eating a diet rich in antioxidants may reduce the risk of many diseases including heart disease, diabetes, some cancers, and age related diseases, antioxidants work to remove free radicals from the body's cells and prevent or reduce damage caused by oxidation, this book is devoted to the basics, concepts, and ideas related to the sources and types of antioxidants and their role in influencing human health
1
Keywords: Analysis -- food; Antioxidants; Composition -- food